Tolerance to Hypoxia Is Promoted by FOXO Regulation of the Innate Immunity Transcription Factor NF-κB/Relish in Drosophila - Barretto, Elizabeth C. (Genetics, 2020)
Exposure of tissues and organs to low oxygen (hypoxia) occurs in both physiological and pathological conditions in animals. Under these conditions, organisms have to adapt their physiology to ensure proper functioning and survival. Here, we define a role for the transcription factor Forkhead Box-O (FOXO) as a mediator of hypoxia tolerance in Drosophila. We find that upon hypoxia exposure, FOXO transcriptional activity is rapidly induced in both larvae and adults. Moreover, we see that foxo mutant animals show misregulated glucose metabolism in low oxygen and subsequently exhibit reduced hypoxia survival. We identify the innate immune transcription factor, NF-κB/Relish, as a key FOXO target in the control of hypoxia tolerance. We find that expression of Relish and its target genes is increased in a FOXO-dependent manner in hypoxia, and that relish mutant animals show reduced survival in hypoxia. Together, these data indicate that FOXO is a hypoxia-inducible factor that mediates tolerance to low oxygen by inducing immune-like responses.